2011
DOI: 10.4236/health.2011.311114
|View full text |Cite
|
Sign up to set email alerts
|

Quit smoking improves gastroesophageal reflux symptoms and quality of life

Abstract: Background: Smoking is considered to be risk factors of gastroesophageal reflux disease (GERD). The present study aimed to reveal whether quit smoking improves GERD symptoms and QOL of patients. Methods: In this prospective study, 33 patients who participated in a 12-week quit smoking program filled out the Frequency Scale for the Symptoms of GERD (FSSG) questionnaire, and SF8 QOL questionnaire. Patients filled out the questionnaires at baseline and during the program at 2 weeks, 4 weeks, 8 weeks and 12 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…One explanation for this might be that smokers in the ICP group may have quit smoking because of dyspepsia which is more common among smokers than non-smokers. Quitting smoking alleviates gastroesophageal reflux symptoms [21]. Our recent study among the same population showed that women in the ICP group had used antacid drugs more often than the controls [16].…”
Section: Discussionmentioning
confidence: 96%
“…One explanation for this might be that smokers in the ICP group may have quit smoking because of dyspepsia which is more common among smokers than non-smokers. Quitting smoking alleviates gastroesophageal reflux symptoms [21]. Our recent study among the same population showed that women in the ICP group had used antacid drugs more often than the controls [16].…”
Section: Discussionmentioning
confidence: 96%